THE CORRELATION BETWEEN HIGH SCHOOL STUDENTS’ GRAMMAR AND WRITING ABILITY - Wayan Seruni Kwanyin Santana; Ida Bagus Nyoman Mantra; Dewa Ayu Ari Wiryadi Joni; Luh Ketut Sri Widhiasih (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2022)
This study aimed at investigating the correlation between high school students’ grammar and writing ability. The study made used of a correlational research design. The study utilized two types of tests, those are grammar test and writing test. This study found that there is a positive correlation between grammar and the writing ability of high school students. Moreover, the study suggests that teachers should intensifies the teaching of grammar and writing to improve students’ language skills. This study implies that grammar and writing ability should be really taught intensively in the classroom.